Gestión financiera del rubro cuentas por cobrar de la empresa Dismero del cantón Babahoyo durante el periodo 2021 – 2022 - Moncada Mora, Jonathan Omar (2024)
The general objective of the case study was to analyze the financial management of accounts receivable of the company Dismero S.A. during the period 2021-2022 in the Babahoyo canton, Ecuador. This case study is part of the research line of "Financial, Administrative, Tax Management, Audit and Control", with a specific focus on "Audit and Control". Quantitative and qualitative methods, including numerical analysis and interviews, were used to obtain a comprehensive understanding of the financial and operational situation. The results revealed an increase in the average collection period and a decrease in the accounts receivable turnover ratio, indicating possible difficulties in collection and credit management. In addition, a worrying increase in the bad debt ratio will be observed during the aforementioned periods. In conclusion, the urgency of reviewing and improving credit and collection policies was highlighted to avoid negative impacts on the company's liquidity and profitability. It is recommended to evaluate credit policies, optimize collection processes and establish a robust monitoring system for overdue accounts to mitigate the risk of bad debts.